Age-specific individual physical fitness markers for elite rowers under regular training - Abramova, T. F.; Nikitina, T. M.; Yakutovich, N. M.; Tarasova, L. V.; Iordanskaya, F. A. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of the age-specific individual physical fitness markers applicable in the modern elite rowing sport. The 17-33 year-old (n=72) rowers, qualified Class I to World Class Masters of Sport with 4-20 years of sport experience were sampled for the study. Comparative analysis of physical fitness, working capacity, energy supply system functionality and strength indices was used to find a set of the most informative age-specific individual physical fitness markers that may be recommended as a basis for the physical-fitness-based selection of the rowers in every age group in the standard training system. The fitness and progress rating criteria are dominated by the following: body mass as a key factor; HR versus oxygen consumption as the key indicator of the cardio-respiratory system functionality and controllability; absolute maximum capacity and performance indices of the oxidizing system; maximal voluntary ventilation; absolute and relative anaerobic threshold indices; and relative strength indices.